Catheter ablation of atrial fibrillation in patients with rheumatoid arthritis. Issue 4 (October 2015) - Wen, Song-Nan; Liu, Nian; Li, Song-Nan; Salim, Mohamed; Yan, Qian; Wu, Xiao-Yan; Wang, Yue; Kang, Jun-Ping; Ning, Man; Wu, Jia-Hui; Ruan, Yan-Fei; Yu, Rong-Hui; et al.
Abstract Background Rheumatoid arthritis (RA) is associated with an increased incidence of atrial fibrillation (AF). This study evaluated the safety and efficacy of catheter ablation (CA) in the treatment of AF in patients with RA, which has not been previously reported. Methods A total of 15 RA patients with AF who underwent CA were enrolled. For each RA patient, we selected 4 individuals (control group, 60 patients in total) who presented for AF ablation in the absence of structural heart or systemic disease and matched the RA patients with same gender, age (±2 years), type of AF, and procedure date. Results Patients with RA had a significantly higher C-reactive protein level (1.81 ± 2.35 mg/dl vs. 4.14 ± 2.30 mg/dl, p = 0.0320), white blood cell count (5632 ± 1200 mm3 vs. 6361 ± 1567 mm3, p = 0.0482), and neutrophil count (3308 ± 973 mm3 vs. 3949 ± 1461 mm3, p = 0.0441). At 2-year follow-up, atrial tachyarrhythmia (ATa) recurrence rate in the RA group (33.3%, 5/15) was similar to that in the control group (31.7%, 19/60; p = 0.579) after single procedure. In all the five patients from the RA group who developed recurrence, ATa relapsed within 90 days following index procedure (median recurrence time 18 days vs. 92 days in control group; p = 0.0373). Multivariate Cox regression analysis showed that hypertension and left atrial diameter but not RA, C-reactive protein, white blood cell count, and neutrophil count were independent predictors of ATa recurrence. Conclusions Catheter ablation of AF can be safely performed in patients with RA, with a success rate comparable to that of patients without RA. RA patients tend to develop early ATa recurrence after AF ablation.